Hubungan Perilaku Kepatuhan Perawat dengan Penerapan Standar Operasional Prosedur (SOP) Kejadian Risiko Jatuh pada Pasien Anak - Muh. Jumaidi Sapwal; Wahyuni, Puri; Fahrozi, Lalu Aries (ProHealth Journal, 2021)
One thing that often happens to pediatric patient is falling. In Indonesia, it is reported that the incidence of falling patients is recorded at 14%, whereas to achieve patient safety is supposed to be 0% of falling patient’s accidence. Children patient who are in health care facilities have a 100% potential risk of falling. To get safety and comfort during the nursing care process, nurses must adhere on fall risk Standard Operating Procedure. This research is a quantitative study by using descriptive correlative with cross sectional design. The samples are 18 respondents for nurses and 18 children patients who are treated in the pediatric room. The Data were collected by using an observation sheet that was carried out on October 2020. Spearman rank statistical analysis was used to see the relationship between the compliance behaviour of nurses in implementing standard operating procedures (SOP) on the incidence of falling risk on children patient. The results of the study showed that there is no relationship between the compliance behaviour of nurses in implementing standard operating procedures (SOP) on the risk of falling patients in the pediatric room at Dr. R. Soedjono Selong hospital with a value of p is 0.608. In conclusion, that there is no relationship between the compliance behaviour of nurses in implementing standard operating procedures (SOP) on the risk of falling patients in the pediatric room. Whereas it was found that nurses' compliance with the standard operational procedure for the incidence of fall risk was 17 people in the moderate category.